A palladium salen complex: an efficient catalyst for the Sonogashira reaction at room temperature. (5th March 2015) - Gogoi, Ankur; Dewan, Anindita; Borah, Geetika; Bora, Utpal
Abstract : A tetradentate Schiff base derived palladium complex works as an efficient catalyst for the room temperature Sonogashira reaction. Abstract : A tetradentate Schiff base derived palladium complex has been developed as a catalyst for the room temperature Sonogashira reaction under copper free conditions. The main catalytic species, a Pd-complex was derived from Schiff base ligand N, N ′-bis(salicylidene)-arylmethanediamine and Pd(OAc)2 . Electron rich, electron deficient and sterically hindered aryl iodides underwent smooth coupling to afford good to excellent yield of diaryl alkynes in isopropanol at room temperature. The protocol is also suitable for aliphatic alkynes.